Pengaruh Persepsi Harga, Lokasi, dan Kualitas Layanan Terhadap Kepuasan Konsumen pada Coffe Shop Tribhuwana Kopi Surabaya - Eva Kharisma Yolandita Manurung; Ugy Soebiantoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the influence of product quality, price, and product variety on purchase decisions on motorcycles at Tribhuwana Kopi Surabaya. The population used in this study is all customers who have bought motorcycles at Tribhuwana Kopi in the city of Surabaya. The sampling technique uses non-probability sampling with the number of samples used as many as 80 respondents. The research method used is a qualitative approach The techniques used in data collection are the distribution of questionnaires and observations. This study uses the SEM PLS 3.0 program to calculate and analyze data. The results of this study show that price has a significant positive effect on customer satisfaction because affordable prices are in accordance with the quality of the products provided which results in increased sales. Location has a significant positive effect on customer satisfaction because location can indicate strategic location and convenience for customers. Service quality has a significant positive effect on customer satisfaction because the company is able to influence consumers in providing satisfaction. The company is expected to maintain the price, location, and quality of service well in order to provide satisfaction for consumers.